2016
DOI: 10.1103/physrevb.94.064303
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen diffusion in bulk and nanocrystalline palladium: A quasielastic neutron scattering study

Abstract: The diffusion dynamics of hydrogen in bulk and nanocrystalline palladium has been examined using quasielastic neutron scattering (QENS). With respect to bulk PdH0.73, two relaxation processes were found. For both processes, the variation of the relaxation times with momentum transfer was well reproduced by a model of jump diffusion between adjacent octahedral sites. Upon cooling the fast relaxation fraction decreases. The result suggests that the slow relaxation corresponds to jumps between the ground states a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 88 publications
(115 reference statements)
1
12
0
3
Order By: Relevance
“…The obtained values arehω 0 = 65 meV for O sites and 146 meV for T sites at h = 0.0%. Notably, the value for the O site at zero strain agrees with previously reported experimental values of 62.4-69 meV [9,61]. This indicates that the anharmonicity of the potential surface around the H-preferred site (i.e., the O site) is effectively incorporated in the present ab initio PIMD calculations by sampling the delocalized states of the H atom.…”
Section: Quantum Distribution Of a H Atomsupporting
confidence: 90%
See 2 more Smart Citations
“…The obtained values arehω 0 = 65 meV for O sites and 146 meV for T sites at h = 0.0%. Notably, the value for the O site at zero strain agrees with previously reported experimental values of 62.4-69 meV [9,61]. This indicates that the anharmonicity of the potential surface around the H-preferred site (i.e., the O site) is effectively incorporated in the present ab initio PIMD calculations by sampling the delocalized states of the H atom.…”
Section: Quantum Distribution Of a H Atomsupporting
confidence: 90%
“…Much attention has focused on clarifying the mechanism of the high diffusivity of H in nanostructured Pd, such as nanocrystalline grain boundaries [6][7][8], nanoparticles [9,10], and dislocation cores [11,12]. Kofu et al [9] recently examined the diffusion dynamics of H in 8-nm Pd nanoparticles using quasielastic neutron scattering and observed a fast relaxation process with the small activation energy of 0.12 eV, in addition to a conventional relaxation process (0.24 eV) inside the PdH 0.47 nanoparticles. The face-centered cubic (fcc) lattice (space group: F m3m) of Pd has two possible interstitial sites for H atoms, i.e., octahedral (O) sites (4b positions in Wyckoff notation) and tetrahedral (T) sites (8c positions).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pd powder used as a bulk sample was obtained from Sigma Aldrich with a specified purity of 99.9 % and the hydrogen gas (purity 99.99 %) from Suzuki Shokan. The Pd nanocrystals used in this work are basically the same as those in the previous heat capacity [54], neutron diffraction [38], and QENS measurements [39]. The nanocrystals were synthesized by the same method descried elsewhere [55].…”
Section: Methodsmentioning
confidence: 99%
“…Our recent neutron diffraction (ND) work on nanocrystalline PdD x (nano-PdD x ) demonstrated that some of H atoms, probably in the subsurface, are accommodated at the tetrahedral (T ) sites (1/4, 1/4, 1/4) [38]. It was also reported by a quasielastic neutron scattering (QENS) study that an additional fast diffusion process of the H atoms appeared in nano-PdH x [39].…”
Section: Introductionmentioning
confidence: 98%